2012
DOI: 10.1371/journal.pone.0038731
|View full text |Cite
|
Sign up to set email alerts
|

HPV Genotype Distribution in Cervical Intraepithelial Neoplasia among HIV-Infected Women in Pune, India

Abstract: BackgroundThe distribution of HPV genotypes, their association with rigorously confirmed cervical precancer endpoints, and factors associated with HPV infection have not been previously documented among HIV-infected women in India. We conducted an observational study to expand this evidence base in this population at high risk of cervical cancer.MethodsHIV-infected women (N = 278) in Pune, India underwent HPV genotyping by Linear Array assay. Cervical intraepithelial neoplasia (CIN) disease ascertainment was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
42
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 38 publications
10
42
2
Order By: Relevance
“…The clearance rates observed in our study was significantly lower than reported in studies (68.3 to 80.7%) among HIV-seronegative women. 4,2225 However previous studies amongst HIV-seropositive women have reported HPV clearance rates that are comparable 16 , higher 4,8,23,26 and even lower 19 than ours. As reported in earlier studies, we too observed lower clearance rates in women having infection with carcinogenic HPV types especially the alpha-9 species, compared to the clearance rate among carcinogenic HPV types.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The clearance rates observed in our study was significantly lower than reported in studies (68.3 to 80.7%) among HIV-seronegative women. 4,2225 However previous studies amongst HIV-seropositive women have reported HPV clearance rates that are comparable 16 , higher 4,8,23,26 and even lower 19 than ours. As reported in earlier studies, we too observed lower clearance rates in women having infection with carcinogenic HPV types especially the alpha-9 species, compared to the clearance rate among carcinogenic HPV types.…”
Section: Discussioncontrasting
confidence: 65%
“…Written, informed consent was obtained from all participants. The description of the study population and the HPV genotyping results at baseline has been published in an earlier report 8 . Participants enrolled in this study were invited to return for clinical follow-up after 12 months of their initial visit.…”
Section: Methodsmentioning
confidence: 99%
“…However, the higher diagnostic accuracy of the molecular methods implemented in our study might have positively affected the sensitivity of the survey, explaining, consequently, the differences found comparing our findings with the results of other studies, which used different diagnostic techniques [19]. Recent epidemiological studies showing high HPV-51 frequency in several geographical areas could support the hypothesis of previous underreporting for some HPV types owing to less sensitive tools [20], [21], [22], [23], [24], [25], even if HPV-51 is frequently detected in co-infection with other types mainly in developing countries, characterized by a higher HPV genotype variability and HIV-infection [26], [27], [28], [29], [30]. Based on this assumption, the epidemiological differences identified in several areas might be reduced in the near future scaling-up new sensitive methods.…”
Section: Discussionmentioning
confidence: 80%
“…We observed that the decrement in sensitivity was more for careHPV testing than for HC2; however, self-sampling does not reduce specificity for care-HPV and only slightly for HC2. The specificity of the OncoE6 for cervical precancer and cancer raises the possibility of its application to screening high HPV-prevalence, high-risk populations, such as for cervical (21)(22)(23)(24)(25) and anal cancer (26) in HIV-infected women and anal cancer in HIV-infected (27)(28)(29) and -uninfected men (30) who have sex with men. VIA is commonly used in low and middle-income countries (LMIC) achieving a moderate sensitivity with low specificity (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%